Human NK Cell Diversity in Viral Infection: Ramifications of Ramification - Strauss-Albee, Dara M.; Blish, Catherine A. (Frontiers in Immunology, 2016)
Natural killer (NK) cells are a unique lymphocyte lineage with remarkable agility in the rapid destruction of virus-infected cells. They are also the most poorly understood class of lymphocyte. A spectrum of activating and inhibitory receptors at the NK cell surface leads to an unusual and difficult-to-study mechanism of cellular recognition, as well as a very high capacity for diversity at the single-cell level. Here, we review the evidence for the role of NK cells in the earliest stages of human viral infection and prevention. We argue that single-cell diversity is a logical evolutionary adaptation for their position in the immune response, and contributes to their ability to kill virus-infected cells. Finally, we look to the future, where emerging single-cell technologies will enable a new generation of rigorous and clinically relevant studies of NK cells accounting for all of their unique and diverse characteristics.